Turismo e desenvolvimento no município de Maragogi/AL: um olhar sobre os processos de participação social, democracia e cidadania - Soares, Artemisia dos Santos (2019)
Maragogi/AL is a coastal municipal, located in the extreme north of the state of Alagoas, equidistant 125 km from two northeastern capitals, Maceió and Recife. Nowadays presents itself as the second receiving pole of tourists from the state. To understand tourism dynamics critically, it was necessary to consider the historically constructed endogenous factors that uniquely characterize the way tourism develops in place, such as the secular exploitation of sugarcane. From this perspective, this study aimed to analyze the process of social participation in the development of tourism in Maragogi/AL, considering the territorial dimension. The specific objectives are: a) To problematize historically the process of sociospatial formation of the northeastern sugarcane zone, highlighting the Zona da Mata Alagoana, particularly the municipality of Maragogi; b) Discuss the socioeconomic implications of public tourism policies in the municipality of Maragogi/AL; and c) To investigate the level of social participation of the population in the dynamics of local tourism. The research was guided by participatory action research, a method of study and action that quest to obtain reliable and useful results to improve collective situations, basing the research on the participation of the owns collectives to investigate. The results indicate that the inequality present in the Brazilian socioeconomic and political dynamic, although not strictly correlated with the tourism activity, has been accentuated through the establishment of development models that question participation, having decentralization of decision-making power, but not deconcentration, that is, the redistribution of income so discursed in the form of social welfare, perpetuating inequalities founded by the sugarcane culture. For the group that played the role of the DRP, tourism and its particularities mostre it selfs like a secondary factor in the list of priorities, because, according to them, there is already directed funds and actions enough to the development of tourism in the municipality, and it is now necessary to apply the economic benefits, resulting from the activity in the social and environmental aspects of the city, seeking to see the place in its territorial complexity aiming at reducing inequalities. Also, there was a aloofness of younger from political issues that directly affect the population in Maragogi, lacking an educational stimulus for democracy. In search of a disruption of reality, of a demystification, this research proposed to take a contradictory position to the presented reality, demystifying the idea of tourism as a “salvation from farming”, while, in reality, it is realized as an exploratory practice of places, when it moves its citizens away from the center of the process, either in decision-making or as enjoying the benefits arising from the activity. Considering a critical perspective, from a complex and inseparable look between research, teaching and extension, the study allowed, as research, the understanding of the context of socio-spatial formation of the maragogiense population, as well as the context of the application of public tourism policies in the municipality; while extension, it invited this population to assume their place of speech within the process of touristification of their place; and, as a teaching, it took the participatory/active methodologies for the pedagogical practice with the young people of the place, initiating a stimulus to the awareness, of building critical reflection about themselves and about the role that it aims that they search assume in history of Maragogi.